Building a Validity Argument for a Listening Test of Academic Proficiency. - Aryadoust, Vahid (Vahid Aryadoust is Lecturer at the Centre for English Language, 2013)
Over the years, various approaches to validation have emerged in psychological and educational assessment research, which can be classified into traditional approaches and modern approaches. Traditional approaches view validity as a multicomponential concept including, for example, content, construct, and predictive validity, while modern approaches conceptualize it as a unitary concept evaluated through argumentation. Drawing on the modern approach, this book builds a validity argument for a ...